(untitled) (Archaeologia Adriatica, 2010)
Three important components mark the problems of glass production in late antiquity and the early medieval period. The first consists of glass finds discovered in excavations of early Christian structures or complexes. The second consists of objects from the settlement strata of a considerable number of excavated medieval sites, some of them with a Roman past (Nin, Bribir…), while the third consists of material from the excavations of early medieval cemeteries. The subject of this discussion is actually the analysis of several exclusive glass items that come from the Early Croatian cemetery at Ždrijac that expand knowledge about late antique and early medieval glass production on the eastern Adriatic coast. The exclusive nature and exceptional value of the objects, as well as the context of the finds as a part of the integral position of Early Croatian prominent families define them as the possessions of elite members of society. The context of the absence of glass finds in the other graves from this period, and the reduced finds in the settlement strata of early medieval sites, suggests that these objects were imported by wealthy members of society, and from this we can indirectly presume a reduction and perhaps a discontinuation of local glass production in the region of ancient Liburnia in the early medieval period. Finds from the cemetery within grave units that can be assigned chronologically on the basis of other luxurious finds to the first half of the 9th century, when elements of Christianization can be noted at this cemetery otherwise characterized by a pagan burial ritual, allow the possibility of interpreting the probable ritual symbolism of these objects. The use of similar typological forms of glass footed goblets as votive lights during the Early Christian period otherwise leads us to consider that in the context of graves 310 and 322 these could perhaps be oil lamps, symbols of the eternal light that accompanies the deceased in the afterlife. In order to establish the possible production provenience and chronological determination for the manufacture of these objects, the reliably dated context of the burials in the first half of the 9th century was set aside, and a deductive analysis was performed of the basic characteristics of the glass grave goods, resulting in the finding that these items represent standard forms of the 6th and 7th centuries. In considering the production origin on the basis of certain analogies with northern Italy, primarily based on the large quantity of related goblets from sites in northern Italy, such as Nocera Umbra, Invilino, Castel Trosino, and also some nearby Slovenian sites, particularly Koper, one cannot a priori reject the previous relating of the glass finds from the Early Croatian cemetery at Ždrijac in Nin specifically to such a northern Adriatic source. However, the analysis of the decorative patterns on the flasks, which are tied to production in eastern Mediterranean workshops, as well as the exceptionally widespread appearance of glass footed goblets throughout the entire Mediterranean, also indicate the relevant possibility of an eastern provenience of these artifacts. The means by which they arrived in the context of the cemetery at Ždrijac are difficult to perceive, but the appearance of these grave goods in grave units from the 9th century shows a renewed interest in glass products, which after the great expansion in the early Imperial period had been greatly reduced in late antiquity and the early medieval period.